Perspectives on the integration of agri-entrepreneurship in tertiary agricultural education in Africa: insights from the AgriENGAGE project - Chirinda, Ngonidzashe; Abdulkader, Bisan; Hjortsø, Carsten Nico; Aitelkadi, Kenza; Salako, Kolawolé Valère; Taarji, Noamane; Mhada, Manal; Lamdaghri, Zidane; Romanova, Gergana; Assogbadjo, Achille Ephrem; Chadare, Flora Josiane; Saidi, Mwanarusi; et al. (Frontiers in Sustainable Food Systems, 2024)
The underperformance of agricultural education systems in Africa is evident through various indicators such as increased unemployment among recent agricultural graduates, inefficiencies in agricultural product value chains, and a decline in enrollment in agricultural schools. The AgriENGAGE project, which included eight African universities, was supported through the Erasmus+ Capacity Building in Higher Education program funded by the European Commission to address these challenges. The project aimed to contribute toward revitalizing agricultural education systems to stimulate agricultural transformation and enhance the sector’s competitiveness while meeting the labor market’s demands. This article draws on lessons learned at eight universities to provide a perspective on agri-entrepreneurship education integration in African universities. We provide descriptions, experiences, and insights on agri-entrepreneurship education integration in partner universities in Kenya, Benin, Morocco, and Uganda. Based on these experiences, we provide perspectives on reducing youth unemployment and improving the effectiveness of agricultural education in contributing to the development of sustainable food systems.